Investigating the Effect of Professors’ education degree, scientific rank, and experience on Classroom Management Styles; Case Study: Kabul University 2020 - Khpalwak, Mohammad Tahir (Journal of Social Sciences - Kabul University, 2023)
The research under the title of Investigating the Effect of Professors' Gender and educational discipline on classroom management styles was conducted at Kabul University. The research method is correlational, applied in terms of purpose, quantitative in terms of information, and field research in terms of location. The research participants are professors of Kabul University, the total number is 907, in this, 717 are men and 190 are women. 270 were selected as a sample. Data were collected by Wolfgang and Glickman's (2008) questionnaire and analyzed using SPSS24. The results showed that the dominant style of the Kabul University professors is (the interventionist style). PhD professors tend to be more in the interactionist style of classroom management and Master and Bachelor assistant professors tend to be more in the interventionist style of classroom management. From the scientific rank, teaching assistant, and assistant professors (higher rank) use Interactionist Style of classroom management, but assistant professors (lower rank), associate professors and professors use the Interventionist Style of classroom management. There was no significant relationship between experience and classroom management styles.